Factors Contributing to Red Blood Cells Crossmatch and Transfusion among Obstetrics Patients in a Single Tertiary Hospital - Noordin, Siti Salmah; Ismail, Amrah; Abdul Karim, Faraizah; Iliassa, Intan Iliana (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Transfusion of blood and blood components among obstetrics patients is a common practice but they are not without risks. This study aims to determine crossmatch to transfusion ratio (C:T ratio) and to assess the factors that influence red blood cells (RBC) transfusion among obstetrics patients in a single tertiary hospital. MATERIAL AND METHODS: This was a retrospective cohort study of RBC crossmatch requests with data collected from 350 obstetrics patients. The patients were grouped into either received RBC transfusion or did not receive transfusion. Demographics and clinical characteristics were analyzed using descriptive and multivariate analysis. RESULTS: The mean C:T ratio was 3.1. Of 350 patients, 149 (42.6%) patients did receive RBC transfusion. Patients with underlying hemoglobinopathy (75.9%), history of postpartum hemorrhage (63.6%), underwent instrumental assisted delivery (64.3%), and with hemoglobin level of < 70 g/L upon crossmatch requests (90.5%) did receive RBC transfusion. Cesarean section (p=0.011), hemoglobin level < 99 g/L (p<0.001), estimated blood loss > 1000 mL (p<0.001), and symptomatic anemia (p=0.029) were the significant factors associated with RBC transfusion. CONCLUSION: The mean C:T ratio in our study was high. Identifying the factors contributing to RBC transfusion among obstetrics patients are important to reduce unnecessary crossmatch and subsequently improve blood inventory management, and thus further reduce the risks associated with allogeneic transfusion.